The Pillars Concept: An Approach for Managing Hypertrophic Concha in Otoplasty - Neves, José Carlos; Arancibia-Tagle, Diego (Facial Plastic Surgery, 2024)
Prominent ear deformities often result from a combination of hypertrophic conchal cartilage and an underdeveloped antihelical fold. Traditional otoplasty techniques, such as antihelical folding sutures and conchal setback maneuvers, may introduce tension and risk of relapse, leading to suboptimal aesthetic outcomes. The Pillars Concept represents an alternative surgical approach specifically designed to address hypertrophic concha, ensuring stable and natural results.This study aimed to present the Pillars Concept as an alternative method for correcting hypertrophic conchal cartilage, highlighting its advantages over traditional techniques, and evaluating its effectiveness in maintaining long-term stability of the ear's position without relapse.A retrospective analysis was conducted on 89 patients who underwent otoplasty utilizing the Pillars Concept. The technique involves selective transection of two supporting pillars located in the superior and inferior conchal regions after partial resection of the hypertrophic concha. This releases the conchal cartilage and enables tension-free repositioning of the auricular framework.Of the 89 cases, no hypertrophic concha recurrences were noted during follow-up periods. Complications were minimal, with only two patients (2.2%) experiencing a sensation of “glued ears” following complete conchal resection. Retroauricular fullness was observed in two cases (2.2%) after conchal setback, primarily due to inadequate management of the residual cartilage length. Patient satisfaction was high, and the natural aesthetic of the auricle was consistently preserved.The Pillars Concept provides a reliable, tension-free method for addressing hypertrophic conchal cartilage in otoplasty, preserving the natural ear anatomy and ensuring long-term stability without the risk of relapse. This technique should be considered a valuable addition to the armamentarium of otoplasty procedures.
Keywords: otoplasty; hypertrophic concha; Pillars Concept; tension-free otoplasty; preservation otoplasty